Teacher code switching in an ESL classroom / Eswary Jayapalan - Eswary , Jayapalan (2019)
Code switching is a linguistic phenomenon related with bilingual and multilingual learners, which is a subject of constant discussion among linguists, educators and policy makers. Code switching by educators and learners are over and over again viewed with suspicion and contempt, which can be attributed to the dominant monolingual misconception that the act of mixing language is a sign of linguistic deficit and incompetence. In the multilingual Malaysian classroom setting, language is central to the construction of meaning for students from different linguistic backgrounds. Code switching is a strategy which is occasionally used by teachers who share the same L1 as the learners, to deliver their instruction to ease the learning process for learners, predominantly low proficiency learners. Thus this study aims to describe patterns and functions of teacher’s code-switching and students’ views towards the teacher’s code-switching behavior in an ESL classroom. This study will then ask the questions, “What are the patterns of the teacher‘s code-switching in the English as a second language classroom?”, “What are the functions of the teacher‘s code-switching in the classroom?” and “How the student view the teacher‘s code-switching behaviour in the classroom?”. The sample of this study is, one teacher and thirty students from an ESL class from an institution in Kuala Lumpur. In this study the method of qualitative approach was used. The data was gathered through classroom observations (audio recordings), interview and questionnaires. The two frameworks; the Matrix Language Frame model by Scotton (1993) and the Conversational Functions by Gumperz (1982) were referred to analyze the data.